2017
DOI: 10.1007/s00436-017-5698-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening of chemical compound libraries identified new anti-Toxoplasma gondii agents

Abstract: Toxoplasma gondii is the etiological agent of toxoplasmosis, a common parasitic disease that affects nearly one-third of the human population. The primary infection can be asymptomatic in healthy individuals but may prove fatal in immunocompromised individuals. Available treatment options for toxoplasmosis patients are limited, underscoring the urgent need to identify and develop new therapies. Non-biased screening of libraries of chemical compounds including the repurposing of well-characterized compounds is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…The Malaria and Pathogen box compounds (https://www.pathogenbox.org/) selected in high throughput screens against malaria and other pathogens were screened to find compounds that hit biological targets shared among apicomplexans 117 . A number of other chemical libraries have been tested against T. gondii to possibly identify new therapeutic compounds [118][119][120][121] , including all FDA approved drugs seeking compounds for repurposing. In addition, screening of compounds that are active against malaria identified relatively few candidates that were effective against T. gondii 122 .…”
Section: Dormant Forms Of Toxoplasma -The Sporozoite and Bradyzoitementioning
confidence: 99%
“…The Malaria and Pathogen box compounds (https://www.pathogenbox.org/) selected in high throughput screens against malaria and other pathogens were screened to find compounds that hit biological targets shared among apicomplexans 117 . A number of other chemical libraries have been tested against T. gondii to possibly identify new therapeutic compounds [118][119][120][121] , including all FDA approved drugs seeking compounds for repurposing. In addition, screening of compounds that are active against malaria identified relatively few candidates that were effective against T. gondii 122 .…”
Section: Dormant Forms Of Toxoplasma -The Sporozoite and Bradyzoitementioning
confidence: 99%
“…It is necessary to explore whether lumefantrine has anti- T. gondii activity in vitro and in vivo . Besides, studies that have shown successful treatment for toxoplasmosis patients are limited, indicating the urgent need to identify and develop new therapies (Adeyemi et al ., 2018) and data about the inhibition of T. gondii using lumefantrine is not available. Therefore, in this study, we evaluated the effect of lumefantrine treatment on T. gondii infection in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…T. gondii is an apicomplexa intracellular protozoa, which has a similar infection mechanism to Plasmodium. However, studies that have shown successful treatment for toxoplasmosis patients are limited, indicating the urgent need to identify and develop new therapies [26]. In addition, data about the inhibition of T. gondii using lumefantrine is not available.…”
Section: Discussionmentioning
confidence: 99%